2018
DOI: 10.5180/jsgoe.34.1_95
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative magnetic resonance imaging investigation of nine cases of broad ligament leiomyoma

Abstract: Objective: We retrospectively investigated the feasibility of using pre-operative magnetic resonance imaging (MRI) findings to diagnose broad ligament myoma. Design: We examined the presence of elongated uterine arteries, evidenced by MRI, in nine cases of broad ligament myoma among the 257 cases of hysterectomy or myomectomy for uterine myoma performed at our institution from April 2015 to November 2017. Results: In five of seven cases (excluding two cases of myoma of 2.5-cm diameter, growing vertically) an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Actually, IL leiomyoma can grow between RL and UA and widen their distance, a characteristic finding in more than 76% of the IL cases examined for this study. A Japanese language article (English abstract available online) reported that elongation of UA by leiomyoma might be a characteristic MR finding for IL leiomyoma [20]. Interobserver agreement was not assessed, but it might be difficult to make an objective assessment of the elongation or displacement of UA or RL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, IL leiomyoma can grow between RL and UA and widen their distance, a characteristic finding in more than 76% of the IL cases examined for this study. A Japanese language article (English abstract available online) reported that elongation of UA by leiomyoma might be a characteristic MR finding for IL leiomyoma [20]. Interobserver agreement was not assessed, but it might be difficult to make an objective assessment of the elongation or displacement of UA or RL.…”
Section: Discussionmentioning
confidence: 99%
“…Only one English language report has described a study of preoperative MRI findings for the differentiation of intraligamentous leiomyoma from subserosal leiomyoma, which examined the ipsilateral ovary position relative to leiomyoma [19]. Several Japanese reports on this issue have described findings of uterine artery, round ligament, bladder, rectum, and feeding vessels, but no report has presented multiple MRI findings [20].…”
Section: Introductionmentioning
confidence: 99%